2009
DOI: 10.4102/jsava.v80i1.162
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and cardiopulmonary effects of acepromazine, midazolam, butorphanol, acepromazine-butorphanol and midazolam-butorphanol on propofol anaesthesia in goats

Abstract: The study was conducted to study the effect of acepromazine and midazolam along with ketamin on haematological parameters in yak. Twelve clinically healthy yaks of either sex and below 2 years of age from yak farm of ICAR-National Research Centre on Yak, Dirang, Arunachal Pradesh were selected for the study. Yak were randomly divided into two groups, Group AK and Group MK i.e. six animals in each group. The animals in Group AK received acepromazine @0.1mg/kg body weight IM followed by ketamine @2.5mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 25 publications
17
33
1
Order By: Relevance
“…It was found that the combination of butorphanol and medetomidine in the present study offered advantages over the reported action of the drug when used alone. Lack of improvement in degree of sedation when butorphanol is combined with midazolam is in agreement with the findings of Dzikiti et al (2009). In P1 group the quality of analgesia was excellent.…”
Section: Resultssupporting
confidence: 80%
“…It was found that the combination of butorphanol and medetomidine in the present study offered advantages over the reported action of the drug when used alone. Lack of improvement in degree of sedation when butorphanol is combined with midazolam is in agreement with the findings of Dzikiti et al (2009). In P1 group the quality of analgesia was excellent.…”
Section: Resultssupporting
confidence: 80%
“…Although midazolam induced heavy sedation in the present study, it was likely that the maximal effect of midazolam was not achieved by the time propofol was administered. Also, the median induction dose of propofol (3.97 mg kg ) previously reported after intramuscular administration of midazolam (Dzikiti et al, 2009), which is further evidence that the maximal sedative effects of midazolam were not achieved by one minute. In an earlier study by Dzikiti et al, 2009 using the same goats as in the present study, a mean propofol dose of 5.3 mg kg -1 was needed for induction in non-premedicated goats and a median propofol dose of 5.1 mg kg -1 was reported in the study by Pablo et al, 1997.…”
Section: Discussionsupporting
confidence: 52%
“…Midazolam has been reported to produce sedation in goats (Stegmann & Bester, 2001;Dzikiti et al 2009) and decrease the induction dose of propofol in goats (Dzikiti et al 2009). In a previous study, the maximal sedative effects of midazolam were observed at 5 minutes following intravenous administration (Stegmann & Bester, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean arterial blood pressure and SpO 2 obtained even after administration of the highest dose of midazolam in this study were within normal physiological limits and were similar to baseline values within a group. It is well documented in literature that midazolam, especially when used alone does not cause significant changes on cardiopulmonary function (Mehlisch, 2002;Dzikiti et al, 2009). It is important to maintain body temperature, blood pressure and tissue oxygenation within normal physiological limits as was done in the present study because hypothermia, severe hypotension and hypoxaemia are all known to reduce isoflurane MAC (Eger, 2002).…”
Section: Article In Pressmentioning
confidence: 94%